1987
DOI: 10.1002/eji.1830170318
|View full text |Cite
|
Sign up to set email alerts
|

LFA‐1 β‐chain synthesis and degradation in patients with leukocyte‐adhesive proteins deficiency

Abstract: The defective membrane expression of the adhesive protein family (LFA-1, Mo1 and p150,93) on leukocytes from certain patients with recurrent bacterial infections was shown to be secondary to the absence of synthesis of mature beta chain that is common to all three antigens (Springer et al., 1984, Lisowska-Grospierre et al., 1986). In all patients, studies of beta-chain biosynthesis that lead to this conclusion were performed using the monoclonal anti-beta chain antibody to isolate the beta subunit. Since this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 13 publications
(7 reference statements)
2
12
1
Order By: Relevance
“…This conclusion is at least partly supported by our findings that the expression levels of all four possible ␣ subunits differed only in quantity, according to the reduction in total levels of ␤ 2 integrin heterodimers, when compared with CD18 wild-type leukocytes; and also by previously published results derived from studies on patients suffering from LAD1 (49,50,64,65). These authors stated that deficiency in ␤ 2 -integrin heterodimers appears to be quantitative rather than qualitative, with two patients expressing ϳ0.5% and one patient 5% of normal amounts of CD18.…”
Section: Figure 8 Induction Of An Allergic Contact Dermatitis In Cd18supporting
confidence: 86%
See 1 more Smart Citation
“…This conclusion is at least partly supported by our findings that the expression levels of all four possible ␣ subunits differed only in quantity, according to the reduction in total levels of ␤ 2 integrin heterodimers, when compared with CD18 wild-type leukocytes; and also by previously published results derived from studies on patients suffering from LAD1 (49,50,64,65). These authors stated that deficiency in ␤ 2 -integrin heterodimers appears to be quantitative rather than qualitative, with two patients expressing ϳ0.5% and one patient 5% of normal amounts of CD18.…”
Section: Figure 8 Induction Of An Allergic Contact Dermatitis In Cd18supporting
confidence: 86%
“…1A). Evidence for a defective association between ␤ 2 integrin ␣-and ␤ 2 -chains potentially caused by a qualitative alteration in the CD18 hypo molecule was not supported by our data, as a deficiency in dimerization will normally lead to internalization of either subunit and, thereby, to a loss of cell surface expression (49,50).…”
Section: Allergic Contact Dermatitiscontrasting
confidence: 72%
“…Association of the a subunit precursor with the (3 subunit precursor is necessary for additional carbohydrate processing and transport to the cell surface. Association with an a subunit was not detectable in any of the LAD patients who synthesize a A subunit precursor (7)(8)(9). After the isolation of cDNA clones encoding the (3 subunit of the leukocyte integrins (10, I 1) it was demonstrated that heterogeneous mutations in the common d subunit give rise to LAD (8,12).…”
Section: Introductionmentioning
confidence: 99%
“…One class of mutation results in no detectable mRNA or protein precursor, while a fourth class of mutation is characterized by the synthesis of trace amounts of ( subunit precursor and low levels of message (8,12). A fifth class of mutation results in synthesis of a (3 subunit that appears normal by SDS-PAGE, but fails to associate with the a subunit (8,9,12,13). This class of mutation could be due to point mutations in a or (3, or could affect a third protein required for their assembly.…”
Section: Introductionmentioning
confidence: 99%
“…mRNA was detected by Northern blotting using a CDI18 gene probe in our patient, as might be expected. A range of abnormalities of the P chain at the mRNA level has been described (Dana et al, 1987;Dimanche et al, 1987;Kishimoto et al, 1987). The detailed molecular pathology in our patient is currently being studied.…”
Section: Preparation Of An Ebv-transformed B Cell Linementioning
confidence: 99%